2019
DOI: 10.1021/acs.est.9b04959
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Dependent Decay of Viruses, but Not Bacteria, in Aerosols and Droplets Follows Disinfection Kinetics

Abstract: The transmission of some infectious diseases requires that pathogens can survive (i.e., remain infectious) in the environment, outside the host. Relative humidity (RH) is known to affect the survival of some microorganisms in the environment; however, the mechanism underlying the relationship has not been explained, particularly for viruses. We investigated the effects of RH on the viability of bacteria and viruses in both suspended aerosols and stationary droplets using traditional culture-based approaches. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
263
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(284 citation statements)
references
References 69 publications
18
263
0
3
Order By: Relevance
“…In recent laboratory testing, aerosolized SARS-CoV-2 remained viable for up tõ 3 h [21] when tested at a relative humidity of 65%. Inactivation studies suggested that survival on surfaces, and in the air, may be further enhanced at relative humidities of less than 50% [40]. These results are consistent with other airborne viruses-including SARS-CoV-1 [21,41], influenza H1N1 [42,43], and MERS-CoV [44][45][46], which also show evidence of airborne transmission.…”
Section: Disease Transmission By Sars-cov-2 Aerosolssupporting
confidence: 74%
“…In recent laboratory testing, aerosolized SARS-CoV-2 remained viable for up tõ 3 h [21] when tested at a relative humidity of 65%. Inactivation studies suggested that survival on surfaces, and in the air, may be further enhanced at relative humidities of less than 50% [40]. These results are consistent with other airborne viruses-including SARS-CoV-1 [21,41], influenza H1N1 [42,43], and MERS-CoV [44][45][46], which also show evidence of airborne transmission.…”
Section: Disease Transmission By Sars-cov-2 Aerosolssupporting
confidence: 74%
“…The dramatic increase in salt concentrations, and/or the time of exposure to high salt concentrations and reduced pH likely cause damage to the virus. This in turn suggests that the evaporation kinetics of suspended droplets on surfaces may affect the survival of viruses, in a similar manner as that suggested in aerosol droplets 24 . Thus, complete dryness could in fact protect the virions from those high concentrations of dissolved salts and low pH 5,19 .…”
Section: Discussionsupporting
confidence: 63%
“…While survival varies between virus species, increased survival at both low (<40%) and very high (>90%) RH is often observed, with decreased survival at intermediate RH levels [20][21][22]25,27 . The underlying mechanism of this U-shaped survival as a function of RH is not clear 24 . Only a few studies have attempted to gain mechanistic understanding of how RH affects virus stability in microdroplets.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations